Soil Creep in Kaliwedi and Randengan Villages: A Preliminary Study - Wahyu Wilopo, Wahyu Wilopo (2011)
Soil creep has occures in Kaliwedi and Randengan Villages of Banyumas District, Central Java, Indonesia since 2008. A number of houses have been totally destroyed, while the remaining property and infrastructures in a total area of 17 hectares are under a serious threat of the soil creep. The occurrence of soil creep is mostly controlled by the geological condition of these areas. Field investigation shows that a clay stone layers exists beneath this area and is likely to be sliding surface of the soil creep. The soil creep is likely to be triggered by rainwater infiltration during the heavy rainfall period, causing the shear strength of soil along the slip surface to reduce. Water from unlined fish ponds and liquid waste of domestic activities, which infiltrate into the ground, are likely to contribute to the decrease in the soil shear strength, causing the soil mass to keep moving even during dry seasons.